Effect of pre-treatments using potassium metabisulphide and alkaline ethyl oleate on the drying kinetics of apricots - Doymaz, I (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2004)
The effect on the drying time of apricot samples investigated, when a pre-treatment applied using a combination of potassium metabisulphide and alkaline ethyl oleate solutions resulted in a reduction in drying time compared to untreated samples. The drying data were fitted to the various thin-layer models. All the models were compared using three statistical parameters, i.e. coefficient of determination r(2), reduced mean square of the deviation chi(2) and root means square error E-RMS. Comparing the r(2), chi(2) and E-RMS values of all models, the logarithmic model represented drying characteristics better than other models. The effective. diffusivity varied from 675.8 to 1261.4 mum(2)s(-1). (C) 2004 Silsoe Research Institute. All rights reserved Published by Elsevier Ltd.
Keywords: AIR; MOISTURE; SUN; Agriculture